2017
DOI: 10.2196/mhealth.7816
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient-Centered Care for Young People in General Practice With a Codesigned Screening App: Mixed Methods Study

Abstract: BackgroundDespite experiencing a high prevalence and co-occurrence of mental health disorders and health-compromising behaviors, young people tend not to seek professional help for these concerns. However, they do regularly attend primary care, making primary care providers ideally situated to identify and discuss mental health and lifestyle issues as part of young people’s routine health care.ObjectiveThe aim was to investigate whether using a codesigned health and lifestyle-screening app, Check Up GP, in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…In addition, it may be possible to identify psychological and social factors influencing health-risk behaviors such as smoking and alcohol consumption [29,30,31,32]. Several studies revealed that the assessment of psychological and social issues during medical consultations is related to positive experience, disclosure, and engagement with care of adolescents and young adults [33,34,35], supporting the current results. Furthermore, the present findings are consistent with a review conducted by Ambresin et al [36] Table 4).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, it may be possible to identify psychological and social factors influencing health-risk behaviors such as smoking and alcohol consumption [29,30,31,32]. Several studies revealed that the assessment of psychological and social issues during medical consultations is related to positive experience, disclosure, and engagement with care of adolescents and young adults [33,34,35], supporting the current results. Furthermore, the present findings are consistent with a review conducted by Ambresin et al [36] Table 4).…”
Section: Discussionsupporting
confidence: 78%
“…The initial interest (78.3%) and uptake (77.8%) in eligible youth patients was high, especially when compared to other trials. For example, less than half of the youth who were approached to use the Check Up GP service accepted the invitation (26). Our higher rates of participation may be due to the youth patients being approached by the practice staff on arrival rather than by the GP (as in mobiletype) or over the phone by practice staff (as in Check Up GP).…”
Section: Service Need and Uptakementioning
confidence: 92%
“…Our higher rates of participation may be due to the youth patients being approached by the practice staff on arrival rather than by the GP (as in mobiletype) or over the phone by practice staff (as in Check Up GP). When considering the short screening period of this trial, the number of youth screened is equivalent to similar youth studies (26,34). Unfortunately, due to the pace of the front-of-practice procedures and lack of access to patient-level data, it was not possible to determine the total number of adolescents who visited the participating GPs during the trial period and were not approached (i.e.…”
Section: Service Need and Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Technology-based screening services for mental illness have now been implemented in various healthcare settings. For adults, the UK's Integrating Mental and Physical healthcare: Research Training and Services (IMPARTS [23]) program and the Australian StepCare [24,25] service provide hospital specialists and GPs with a tool to screen patients' mental health symptoms prior to their appointment, with results integrated into medical software for immediate review. Both services were found to be acceptable for use among practitioners and patients and feasible to implement within their intended clinical context [23][24][25].…”
Section: Introductionmentioning
confidence: 99%